Blue thermally activated delayed fluorescence emitter using modulated triazines as electron acceptors. (January 2020) - Lee, Youngnam; Woo, Seung-Je; Kim, Jang-Joo; Hong, Jong-In
Abstract: Three types of thermally activated delayed fluorescence (TADF) emitters, namely, moTrSAc, tmTrSAc, andmotmTrSAc, are reported that emit blue-shifted emission with high external quantum efficiencies (EQEs). These emitters have electron donating spiroacridine in common and various triazine-based electron acceptors. The electronic and structural control on the electron acceptor moiety adjusts the reduction potential of the molecule to shift the emission wavelength to the blue region. Moreover, as these emitters become widened, the light out-coupling efficiency increases due to the enhanced horizontal emitting dipole orientation. As a result, OLEDs based onmoTrSAc, tmTrSAc, andmotmTrSAc emit blue light in a range of 460–480 nm with high EQEs of 21.3, 15.5, and 19.5%, respectively. Graphical abstract: Image 1 Highlights: We synthesized triazine-based thermally activated delayed fluorescence (TADF) emitters, moTrSAc, tmTrSAc, andmotmTrSAc . Modulations of the triazine moiety shifted the emission wavelength and increased the light out-coupling efficiency. moTrSAc, tmTrSAc, andmotmTrSAc -based OLEDs showed blue-shifted emission and high EQEs. Modulations of the triazine electron acceptor moiety can be a strategy to shift the emission wavelength to the blue region while maintaining EQEs.